Complications in proximal humeral fractures. (October 2016) - Calori, Giorgio Maria; Colombo, Massimiliano; Bucci, Miguel Simon; Fadigati, Piero; Colombo, Alessandra Ines Maria; Mazzola, Simone; Cefalo, Vittorio; Mazza, Emilio
Abstract: Necrosis of the humeral head, infections and non-unions are among the most dangerous and difficult-to-treat complications of proximal humeral fractures. The aim of this work was to analyse in detail non-unions and post-traumatic bone defects and to suggest an algorithm of care. Treatment options are based not only on the radiological frame, but also according to a detailed analysis of the patient, who is classified using a risk factor analysis. This method enables the surgeon to choose the most suitable treatment for the patient, thereby facilitating return of function in the shortest possible time. The treatment of such serious complications requires the surgeon to be knowledgeable about the following possible solutions: increased mechanical stability; biological stimulation; and reconstructive techniques in two steps, with application of biotechnologies and prosthetic substitution.